Prasa Pomorza Zachodniego (z lat 1945-1956) o kulturalnym awansie "mas pracujących" w Polsce Ludowej. Z dziejów komunistycznej propagandy na Pomorzu Zachodnim = Press from Western Pomerania (years 1945-1956) on cultural promotion of "working masses" in People's Poland. - Urbanowicz, Adam Andrzej (Zielona Góra: "Pro Libris" Wydawnictwo Wojewódzkiej i Miejskiej Biblioteki Publicznej w Zielonej Górze)
As a result of World War II, the Communists came to power in Poland. One of their goals was to gain legitimacy for their rule by gaining social acceptance. The state-controlled media, especially the press, was supposed to convince the society to follow the new government. Local newspapers published in Western Pomerania were part of the governmental propaganda. In the years 1945-1956, the press propaganda tried to convince the Polish society about the fundamental improvement of its existence in the conditions created by the new communist government. One of the breakthrough areas was supposed to be culture. It was argued that "the masses of workers and peasants" obtained access to it. It was seen as possible through the dissemination of education. As the result, the workers and peasants gained general access to books and newspapers. It was claimed by the propaganda that the People's Republic of Poland definitely exceeded the Second Polish Republic, as well as the modern western European countries and the United States of America, in terms of the dissemination of education and culture.
Keywords: dostęp do kultury; komunizm; Pomorze Zachodnie; prasa; propoaganda; access to culture; communism; Western Pomerania; press